Bake-hardenable Mg–Al–Zn–Mn–Ca sheet alloy processed by twin-roll casting. (1st October 2018) - Bian, M.Z.; Sasaki, T.T.; Nakata, T.; Yoshida, Y.; Kawabe, N.; Kamado, S.; Hono, K.
Abstract: Mg–1.3Al–0.8Zn–0.7Mn–0.5Ca (wt.%) (AZMX1110) alloy sheet produced by low-cost twin-roll casting process exhibits excellent room temperature formability with a large Index Erichsen (I.E.) value of 7.8 mm at room temperature in a solution treated condition (T4). The large I.E. value is associated with a weak basal texture in the T4-condition. This alloy shows rapid age-hardening response at 170 °C, resulting in a significant increase of the flow stress from 198 MPa to 238 MPa within 20 min; such bake hardenability (BH) has never been explored in magnesium sheet alloys before. The microstructure of the bake-hardened sample, characterized by a correlative transmission electron microscopy and atom probe tomography (TEM-APT), reveals that Al, Zn and Ca atoms are segregated to basal dislocations and contribute to the strengthening by pinning dislocation motions, along with the co-clustering of these atoms. This first BH Mg sheet alloy composed of only ubiquitous elements is highly attractive for application to automotive bodies. Graphical abstract: Image 1